Ask a question
0 0


I need help solving this equation. Thank You
Tutors, please sign in to answer this question.

3 Answers

Hi again Pj;
Let's combine like terms on both sides...
Let's isolate x...
Let's subtract 5 from both sides...
Let's subtract 2x from both sides...
Let's divide both sides by 6...
Let's check our results in the original equation...
Let's substitute x with 3...
It works!
This equation isn't too bad. Just a couple steps and I bet you'll recognize what to do quickly.
12x+9-4x-4 = 3x-7-x+30
Step 1) Combine like terms 
*If I think of the equation as having a left side and a right side (split by the = sign), I'm going to combine the similar terms on the left and right.
LEFT: 12x+9-4x-4  ---->8x+5          (I did 12x-4x and 9-4)
RIGHT: 3x-7-x+30 -----> 2x+23       (3x-1x and -7+30)
So now we have 8x+5 = 2x+23   (The variable is on both sides of the = sign) (Not good)
Step 2) Eliminate one of the variables
8x+5 = 2x+23   (I'm going to subtract 2x from both sides to get rid of one variable
-2x      -2x
6x+5 = 23   (Now it's just a two-step equation, easy!)
    -5     -5
6x=18  -----> x=3
**Don't forget to check!
12(3)+9-4(3)-4   =  3(3)-7-3+30
29 = 29 (Correct!)
To solve this equation, we need to combine all of constants and the x terms on each side of the equation:
12x + 9 - 4x - 4 = 3x - 7 - x + 30
8x + 5 = 2x + 23
Now, we subtract 5 from both sides and subtract 2x from both sides:
6x = 18
Now we divide both sides by 6
x = 18/6
x = 3